Novel Tick-Borne Anaplasmataceae Genotypes in Tropical Birds from the Brazilian Pantanal Wetland - Alabí Córdova, Amir Salvador [UNESP]; Fecchio, Alan; Calchi, Ana Cláudia [UNESP]; Dias, Clara Morato [UNESP]; Mongruel, Anna Claudia Baumel [UNESP]; das Neves, Lorena Freitas [UNESP]; Lee, Daniel Antonio Braga [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (MDPI, 2024)
Despite numerous reports of Anaplasmataceae agents in mammals worldwide, few studies have investigated their occurrence in birds. The present study aimed to investigate the occurrence and molecular identity of Anaplasmataceae agents in birds from the Pantanal wetland, Brazil. Blood samples were collected from 93 different species. After DNA extraction, samples positive for the avian β-actin gene were subjected to both a multiplex quantitative real-time (q)PCR for Anaplasma and Ehrlichia targeting the groEL gene and to a conventional PCR for Anaplasmataceae agents targeting the 16S rRNA gene. As a result, 37 (7.4%) birds were positive for Anaplasma spp. and 4 (0.8%) for Ehrlichia spp. in the qPCR assay; additionally, 13 (2.6%) were positive for Anaplasmataceae agents in the PCR targeting the 16S rRNA gene. The Ehrlichia 16S rRNA sequences detected in Arundinicola leucocephala, Ramphocelus carbo, and Elaenia albiceps were positioned closely to Ehrlichia sp. Magellanica. Ehrlichia dsb sequences detected in Agelasticus cyanopus and Basileuterus flaveolus grouped with Ehrlichia minasensis. The 16S rRNA genotypes detected in Crax fasciolata, Pitangus sulphuratus and Furnarius leucopus grouped with Candidatus Allocryptoplasma. The 23S-5S genotypes detected in C. fasciolata, Basileuterus flaveolus, and Saltator coerulescens were related to Anaplasma phagocytophilum. In conclusion, novel genotypes of Anaplasma, Ehrlichia, and Candidatus Allocryptoplasma were detected in birds from the Pantanal wetland.
Keywords: Anaplasmaspp; avian hosts; CandidatusAllocrytoplasma spp; Ehrlichiaspp; South America; tick-borne diseases